Analisis Penerapan Sistem Pengendalian Internal dalam Menjaga Keamanan Investasi Anggota KSP Kopdit Obor Mas Cabang Pasar Tingkat - Malika, Maisya; Dekrita, Yosefina Andia; Mitan, Wilhelmina (Jurnal Projemen UNIPA, 2026)
This internship report analyzes the implementation of internal control systems in safeguarding member investments at KSP Kopdit Obor Mas Pasar Tingkat Branch. The study was conducted from August 1 to December 19, 2025, using observation, interview, and documentation methods. The internal control system analyzed refers to the COSO framework, which includes five main components: control environment, risk assessment, control activities, information and communication, and monitoring. The findings indicate that KSP Kopdit Obor Mas has implemented an internal control system to protect member assets and investments; however, weaknesses were identified in several aspects, such as cases of misappropriation of member savings by employees, highlighting the need for strengthening internal control policies. These findings emphasize the importance of an effective internal control system in maintaining member trust and the operational sustainability of credit cooperatives. This report provides improvement recommendations to enhance the effectiveness of the internal control system to minimize the risk of fund misappropriation and increase the security of member investments.